2015
DOI: 10.1016/j.ces.2015.01.066
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modelling of batch sedimentation subject to slow aggregate densification

Abstract: This version is available at https://strathprints.strath.ac.uk/52030/ Strathprints is designed to allow users to access the research output of the University of Strathclyde. Unless otherwise explicitly stated on the manuscript, Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Please check the manuscript for details of any other licences that may have been applied. You may not engage in further distribution of the material for any pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…In the case of interest in the current section, i.e. ungelled suspensions, flocs must be not in contact with one another so ϕ=ϕ agg must be strictly less than a close packing fraction (that following Usher et al (2009) and Zhang et al (2015) is assumed to equal 0.6).…”
Section: Kynch Theory In the Presence Of Aggregate Densificationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of interest in the current section, i.e. ungelled suspensions, flocs must be not in contact with one another so ϕ=ϕ agg must be strictly less than a close packing fraction (that following Usher et al (2009) and Zhang et al (2015) is assumed to equal 0.6).…”
Section: Kynch Theory In the Presence Of Aggregate Densificationmentioning
confidence: 99%
“…where (Zhang et al, 2013a(Zhang et al, , 2015 a 0 ¼ 3:7914 Pa, m ¼0.0363, n 0 ¼ 10:8302 and ϕ cp ¼ 0:8. Moreover ϕ g;0 ¼ 0:1 is the undensified gel point: observe that this is 0.6 times ϕ agg;0 .…”
Section: Buscall and White Theory In The Presence Of Aggregate Densifmentioning
confidence: 99%
“…At equilibrium, the sample has stopped compressing for a given applied pressure i.e., the compressive yield stress Py( ∞ ), at the equilibrium solids volume fraction can be thus equated to the applied pressure (de Kretser et al, 2001;Green et al, 1996;Landman et al, 1995). Zhang et al (2015b) states that the compressive yield stress can exhibit different types of variation in the neighborhood of the gel point, . Zhang et al (2015a) suggested an empirical equation to fit the compressive yield stress Py( ) as shown in equation 1.…”
Section: Compressive Yield Stress Py( )mentioning
confidence: 99%
“…∞ (Zhang et al, 2015b). Moreover, C0 measured in Pa, b0 and k0 which are dimensionless parameters that are dependent on the suspension properties.…”
Section: Introductionmentioning
confidence: 99%
“…Conventionally, there are many types of separation methods to capture particles dispersed in liquid; for example, filtering (Lorenzen et al, 2014;Ong et al, 2014;Iritani et al, 2015;Sugiyama et al, 2015;Sun et al, 2015), sedimentation (Durst and Raszillier, 1989;Tambun et al, 2012;Zhang et al, 2015), centrifugation (Cao et al, 2014;Zhu and Liow, 2014;Teduka and Nishioka, 2015), and so forth: These separation methods have been extensively developed. Nevertheless, it is not possible to use filtering when there is no clear difference in the particle sizes.…”
Section: Introductionmentioning
confidence: 99%